1
$\begingroup$

I am given $3x^2(x+2)y''+7xy'-2y=0, x \geq 0$. I am asked to solve this differential equation with a series solution around $x=0$. Note, however that $x=0$ is a regular singular point since:

$$ P(x) = 3x^2(x+2) \implies 3(0)^2(0+2)= 0, $$ $$ \lim_{x \to 0}x\frac{Q(x)}{P(x)} = \lim_{x \to 0}x\frac{7x}{3x^2(x+2)} = \frac{7}{6} \text{ and} $$ $$ \lim_{x \to 0}x^2\frac{R(x)}{P(x)} = \lim_{x \to 0}x^2\frac{-2}{3x^2(x+2)} = -\frac{1}{3} $$ are both finite. Thus we assume a solution of the form

$$ y = \sum_{n=0}^\infty a_n x^{n+r}, y' = \sum_{n=0}^\infty a_n(n+r) x^{n+r-1}, \\y''= \sum_{n=0}^\infty a_n(n+r)(n+r-1) x^{n+r-2} $$

Which, after some algebra, yields the indicial equation $$ (2r+1)(3r+5)=0 \implies r_1 = -\frac{1}{2}, r_2 = -\frac{3}{5} $$ And the recurrence relation $$ a_n=-\frac{-3a_{n-1}(n-3/2)(n-5/2)}{(6n+1)(n-1)}, \text{for} \ n \geq 1 $$ and $a_0$ is arbitrary. However, I soon realized that $a_1$ is undetermined as the denominator becomes 0. I was wondering if I got my algebra wrong or the entire approach is not correct. Thanks

$\endgroup$
  • $\begingroup$ I suppose that you made some mistake since you should have $r_1=-\frac 23$ and $r_2=\frac 12$ (hoping no mistake on my side). $\endgroup$ – Claude Leibovici Sep 25 '18 at 8:03
  • $\begingroup$ This is a differential equation of the second order and I expect that you should be able to pick two constants freely (like $a_0$ and $a_1$), not just one. All other values can be evaluated from the recurrence relation. $\endgroup$ – Oldboy Sep 25 '18 at 8:52
1
$\begingroup$

The collected coefficients for the power $n+r$ are $$ 0=6(n+r)(n+r-1)a_n+3(n+r-1)(n+r-2)a_{n-1}+7(n+r)a_n-2a_n\\ =[6(n+r)^2+(n+r)-2]a_n+3(n+r-1)(n+r-2)a_{n-1} $$ with the convention that $a_{-1}=0$. Then the indicial equation for $n=0$ is $$ 0=6r^2+r-2=(2r-1)(3r+2) $$ with recursion $$ a_n=-\frac{3(n+r-1)(n+r-2)}{(2n+2r-1)(3n+3r+2)}. $$ The recursion for $r=\frac12$ reduces to $$ a_n=-\frac{3(2n-1)(2n-3)}{4n(6n+7)}a_{n-1}, $$ and for $r=-\frac23$ $$ a_n=-\frac{(3n-5)(3n-8)}{3n(6n-7)}a_{n-1}. $$ This gives totally problem free recursions for the coefficient sequences of the two basis solutions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.